2020
DOI: 10.7454/hubs.asia.2070220
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personality and Self-Motivation in Political (Dis)Engagement

Abstract: Perceived loss of control of ones' political environment breeds cynicism and lowered self-motivation for future political action, all of which are marked indicators of learned helplessness. This leads to disengagement of a country's people in political activity, thus leaving the government unaccountable and unregulated, while allowing corruption and selfserving policies to plague the nation's well-being. Therefore, this study aimed to better understand the associations among political apathy, learned helplessn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Article from Meng and Berezina (2020) is about personality and political behavior. The study reported that personality trait of extraversion reduced political apathy.…”
Section: A Note From Handling Editormentioning
confidence: 99%
“…Article from Meng and Berezina (2020) is about personality and political behavior. The study reported that personality trait of extraversion reduced political apathy.…”
Section: A Note From Handling Editormentioning
confidence: 99%